Implementation of district-based clinical specialist teams in South Africa: Analysing a new role in a transforming system - Kafayat Oboirien; Bronwyn Harris; Jane Goudge; John Eyles (BMC, 2018)
Abstract Background Improving the quality of health care is a national priority in many countries to help reduce unacceptable levels of variation in health system practices, performance and outcomes. In 2012, South Africa introduced district-based clinical specialist teams (DCSTs) to enhance clinical governance at the lowest level of the health system. This paper examines the expectations and responses of local health system actors in the introduction and early implementation of this new DCST role. Methods Between 2013 and 2015, we carried out 258 in-depth interviews and three focus group discussions with managers, implementers and intended beneficiaries of the DCST innovation. Data were collected in three districts using a theory of change approach for programme evaluation. We also embarked on role charting through policy document review. Guided by role theory, we analysed data thematically and compared findings across the three districts. Results We found role ambiguity and conflict in the implementation of the new DCST role. Individual, organisational and systemic factors influenced actors' expectations, behaviours, and adjustments to the new clinical governance role. Local contextual factors affected the composition and scope of DCSTs in each site, while leadership and accountability pathways shaped system adaptiveness across all three. Two key contributions emerge; firstly, the responsiveness of the system to an innovation requires time in planning, roll-out, phasing, and monitoring. Secondly, the interconnectedness of quality improvement processes adds complexity to innovation in clinical governance and may influence the (in) effectiveness of service delivery. Conclusion Role ambiguity and conflict in the DCST role at a system-wide level suggests the need for effective management of implementation systems. Additionally, improving quality requires anticipating and addressing a shortage of inputs, including financing for additional staff and skills for health care delivery and careful integration of health care policy guidelines.